(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to find the effectiveness of the employee satisfaction level towards the recruitment processes of organization and also to assess the impact of recruitment process on organizational performance. The findings of the study helps to improvise the strategies to make the recruitment process effective. The sample for this study is collected nearly from 100 employees at MSys Technologies were personally surveyed with a structured questionnaire. Based on the investigation in recruitment, research questions were answered. In this study Descriptive Research Design and inferential analysis was used as the sampling procedure and data obtained were statistically analyzed using Chi-square test, one way Anova, Co-efficient of correlation. The analysis and interpretation helps to identify the findings and suggestions of the workers. The more objective the recruitment criteria, the better the organization’s performance.